EKSLUSIVITAS GELAR HABIB: TRADISI, KONTROVERSI DAN SOLUSI AL-QUR’AN BAGI UMAT - Masyhadi, Ahmad Aziz; Fahimah, Siti; Tasmuji (MADINAH, 2025)
Currently, the debate surrounding the lineage of the Habib is becoming increasingly widespread. However, in its present development, this issue has turned into a platform for mutual hostility. Therefore, a middle ground is needed to prevent the discourse on lineage from becoming more uncontrolled. The Qur'an can serve as a solution to strengthen the unity of the Muslim ummah. Using a literature-based approach and critical analysis of Qur'anic evidence, this study investigates the exclusivity of the title Habib within tradition and controversy. The study examines the established traditions and the associated controversies, offering Qur'anic solutions to address this phenomenon—particularly in promoting equality, Islamic brotherhood (ukhuwah Islamiyah), and social justice. It is also expected to provide a more objective understanding of the position and role of the Habib within Muslim society, as well as to develop a more inclusive method for fostering communal harmony. This study positions the Qur'an—the holy book—as a source of guidance for morality and brotherhood, teaching that the most honorable person in the sight of Allah is the most pious one. The Qur'an can thus be a unifying force for Muslims. Through the approach of library research and critical analysis of Qur'anic arguments, this study reconstructs the traditions and controversies surrounding the Habib title based on Qur'anic principles in order to prevent uncontrolled discourse that could undermine the harmony of the ummah.